2013
DOI: 10.1111/j.2047-2927.2012.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of progestin and the progesterone receptor in the suppression of spermatogenesis in rodents

Abstract: SUMMARYSynthetic progestins such as levonorgestrel (LNG) are used in combination with testosterone (T) in male contraceptive clinical trials to suppress gonadotropins secretion, but whether progestins have additional direct effects on the testis are not known. This study aimed to examine the effect of a potent progestin, (LNG), alone or in combination with testosterone (T) on spermatogenesis in adult rats, and to evaluate the functional role of the progesterone receptors (PRs) in the testis. In comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…FSH promotes spermatogenesis (Kumar et al, 2003). The imbalance of reproductive hormones could lead to a series of target organ responses (Lue et al, 2013;Rey et al, 2013;Ribeiro et al, 2013;Szafarowska et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…FSH promotes spermatogenesis (Kumar et al, 2003). The imbalance of reproductive hormones could lead to a series of target organ responses (Lue et al, 2013;Rey et al, 2013;Ribeiro et al, 2013;Szafarowska et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…S4B). The PR knockout mice show increased sperm production (23), suggesting that the up-regulation of PR in the TAp73 KO testes could be associated with defective spermatogenesis. , and p53 Saos-2 tet-on cells were exposed to 2 μM doxycycline for 16 h, followed by qPCR determinations of the indicated mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously demonstrated that PR is expressed in the mammalian testis and the expression is downregulated in testis of infertile men [2,17,20,25,37,38]. In the present study, we tested if loss of PR was due to any sequence alterations in the PR gene and may be a cause of oligo or azoospermia.…”
Section: Discussionmentioning
confidence: 89%
“…PRs are also detected in testis of other mammals [17,20,25] suggesting that progesterone may regulate spermatogenesis. While PR knockout mice (PRKO) have larger testes, greater sperm production, increased numbers of Sertoli and Leydig cells [25]; in humans, PR mRNA and protein are reduced in testis of azoospermic men with maturation arrest and hypospermatogenesis [2,16] and also in spermatozoa of oligoasthenoteratozoospermic infertile men [12]. These observations are definitive evidence to suggest that PR has a role in regulation of spermatogenesis and reduced PR expression is associated with defective spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation